2015
DOI: 10.1016/j.ijheatfluidflow.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Transverse jet-cavity interactions with the influence of an impinging shock

Abstract: A copy can be downloaded for personal non-commercial research or study, without prior permission or chargeThe content must not be changed in any way or reproduced in any format or medium without the formal permission of the copyright holder(s) hold the flow and stabilise the combustion, is one mechanism which has attracted much attention, requiring further research to study the unsteady flow features and interactions occurring within the cavity. In this study we combine the transverse jet injection upstream of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In our previous studies, the influence of shock wave on the supersonic mixing in scramjet engines are simulated, and we observed that the impinging shock wave diminishes the penetration and enhances the mixing of the injectants irrespective of the molecular weights. Schetz et al [19] Zare-Behtash et al [20] observed similar results on this topic.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…In our previous studies, the influence of shock wave on the supersonic mixing in scramjet engines are simulated, and we observed that the impinging shock wave diminishes the penetration and enhances the mixing of the injectants irrespective of the molecular weights. Schetz et al [19] Zare-Behtash et al [20] observed similar results on this topic.…”
Section: Introductionmentioning
confidence: 58%
“…Although single transverse jet is considered as an efficient model for the injection of fuel in supersonic combustion chambers and scientists have been extensively focused [14][15][16][17][18][19][20][21][22][23][24][25], little works have been performed to reveal the main feature of the interaction between the transverse microjets of two different gases. Moreover, various studies focused on detailed perceptive in the vicinity of flow structure in a single jet-supersonic cross flow [19][20][21][22][23][24][25][26][27] and there is little work on the mixing of the combination of the micro fuel jet with micro air jets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies using different types of flow control [68][69][70] have shown this can produce promising results. There has been some interest in the application of LAFPA's to augment the shear layer resonance of supersonic cavity flows.…”
Section: Applications Of Lafpa'smentioning
confidence: 92%
“…attention [20] [21] [22] [23] [24], and an enhanced mixing level can be achieved with an increased residence time when an incident shock wave impinges close to the transverse jet injection location [25]. Thus, it is necessary to evaluate the influence of the incident shock wave on the mixing process in the transverse injection flow field.…”
mentioning
confidence: 99%